2022
DOI: 10.1002/jor.25396
|View full text |Cite
|
Sign up to set email alerts
|

Patellofemoral joint load and knee abduction/adduction moment are sensitive to variations in femoral version and individual muscle forces

Abstract: Torsional profiles of the lower limbs, such as femoral anteversion, can dictate gait and mobility, joint biomechanics and pain, and functional impairment. It currently remains unclear how the interactions between femoral anteversion, kinematics, and muscle activity patterns contribute to joint biomechanics and thus conditions such as knee pain. This study presents a computational modeling approach to investigating the interactions between femoral anteversion, muscle forces, and knee joint loads.We employed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 46 publications
3
10
1
Order By: Relevance
“…This is in agreement with the observed increases in rectus femoris forces in our models with large AVA. Combining our ndings with the results from Wheatley et al 57 further supports the hypothesis that higher rectus muscle forces counterbalance the increased hip extensor muscle moments in models with large AVA (summarized in detail above), leading to increased knee and patellofemoral joint contact forces.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is in agreement with the observed increases in rectus femoris forces in our models with large AVA. Combining our ndings with the results from Wheatley et al 57 further supports the hypothesis that higher rectus muscle forces counterbalance the increased hip extensor muscle moments in models with large AVA (summarized in detail above), leading to increased knee and patellofemoral joint contact forces.…”
Section: Discussionsupporting
confidence: 89%
“…In another paper they showed that the patient-speci c gait pattern reduces hip loading in children with increased AVA 20 . Heller et al 21 showed that increasing the AVA increases hip joint contact forces when tracking the same kinematics, which was con rmed by recent simulation studies [22][23][24] . Increased hip and patellofemoral loading was found in children with increased AVA and normal foot progression angle 25 , whereas decreased hip and knee loads were observed in children with increased AVA and internal foot progression angle compared to healthy control participants 26 .…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…A recent simulation study [28] investigated the impact of femoral AVA on patellofemoral joint loads. The authors found increased patellofemoral loads when AVA was increased from 22° to 42°, whereas a decrease in joint load was observed for the model with an AVA of 52°.…”
Section: Discussionmentioning
confidence: 99%
“…In another paper they showed that the patient-speci c gait pattern reduces hip loading in children with increased AVA [24]. Heller et al [25] showed that increasing the AVA increases hip joint contact forces when tracking the same, subject-speci c motion capture data of four patients with a total hip arthroplasty, which was con rmed by recent simulation studies [26][27][28]. Increased hip and patellofemoral loading was found in children with increased AVA and normal foot progression angle [29], whereas decreased hip and knee loads were observed in children with increased AVA and internal foot progression angle compared to healthy control participants [30].…”
Section: Introductionmentioning
confidence: 86%